An empirical formulation for predicting the ultimate strength of stiffened panels subjected to longitudinal compression - Kim, D.K. (Elsevier Ltd, 2017)
There are several methods such as experimental, numerical, and analytical methods which are the mostly adopted in the verification of proposed design code or guidelines to calculate the ultimate strength performance of stiffened panel structures. This study proposes an advanced empirical formula shape, which is a function of plate slenderness ratio and column slenderness ratio with two (2) correction coefficients (C1 and C2), used to predict the ultimate strength performance of stiffened panel structures in ships. In addition, the two aforementioned correction coefficients were decided and verified by obtaining the result of an ANSYS nonlinear finite element analysis. An average level of initial imperfection and 2 bay – 2 span (1/2 – 1 – 1/2) model were adopted in the proposed empirical formula. The effects of residual strength were not considered in this study. A total of 124 stiffened panels with four different plate slenderness ratios (β) and changing column slenderness ratio (λ) were selected for the simulation scenarios. To confirm the accuracy of the obtained formula, a statistical analysis was also conducted on the ANSYS results and other existing formulas. The proposed method and its details were documented. © 2017